Impact of Various Parameters as Predictors of The Success Rate of In Vitro Fertilization - Dabbagh Rezaeiyeh, Radin; Mehrara, Arian; Mohammad Ali Pour, Amin; Fallahi, Jafar; Forouhari, Sedighe (International journal of fertility & sterility, 2022)
A woman who is infertile is defined as a woman who is unable to conceive after having unprotected sex for more than one year. 20-25% of couples worldwide suffer from infertility each year (60 to 80 million couples). fertilization (IVF) plays a significant role in the treatment of various types of infertility, including fallopian tube defects, endometriosis, immunity, and male causes. IVF is a complex procedure that can be used to aid fertility or prevent genetic problems in the fetus. The objective of this review is to investigate factors that affect IVF failure and success rates. Need for this review is predicated on the different results obtained from previous studies, the high prevalence of infertility, and the lack of a similar study in this field. Articles were regarded as suitable if they evaluated the association between any factor and IVF outcome. A comprehensive search of databases was completed from their inception until March 2021. Our search resulted in 1278 articles. After assessing the titles and abstracts, we selected 70 articles for further reading. Our review shows that the effectiveness of IVF treatment depends on many factors. These include the physical environment, genetics, psychological factors, serum levels of certain hormones, sperm characteristics, as well as the age and body mass index of couples. Based on the results of our study, nutrient supplementation maybe beneficial for the enhancement of semen quality. For better IVF outcome, it is better for obese women to balance their body mass index (BMI) before IVF procedure initiation.